The Evolution of Rehabilitation and Return to Sport Following Cartilage Surgery - Snehal Patel; William Marrone (North American Sports Medicine Institute, 2023)
Rehabilitation after knee cartilage repair or restoration can be a challenging and nuanced process. Historically, conservative rehabilitation protocols have been characterized by limited weightbearing and restricted range of motion (ROM) were created to primarily protect the repaired cartilage but did little for progression into higher level activity. Recent literature has supported accelerated protocols in a variety of cartilage procedures ranging from osteochondral allograft (OCA) Osteochondral autograft surgery (OATS) to matrix-based scaffolding procedures such as Matrix Induced Chondrocyte Implantation (MACI) or Denovo procedures. Advances in technology such as blood flow restriction (BFR) and testing equipment with progressive rehabilitation from the acute phase through the return to sport continuum have made it possible to return to a higher level of activity and performance than first thought of for these procedures. This clinical viewpoint discusses the evolution of knee cartilage rehabilitation characterized by early but progressive weightbearing and early ROM while maintaining early homeostasis in the knee, and then its progression to return to sport and performance in the higher-level athlete. # Level of evidence V